2018
DOI: 10.1186/s12944-018-0935-x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized, double-blinded, placebo-controlled study on safety and tolerability of the krill powder product in overweight subjects with moderately elevated blood pressure

Abstract: BackgroundKrill powder is rich in bioactive ingredients such as eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), phospholipids, protein and astaxanthin. Containing dominantly EPA, it is considered to be effective in lowering lipids, foremost serum triglycerides and LDL cholesterol. Krill-derived protein hydrolysates/peptides may have positive effect on blood pressure and astaxanthin has anti-oxidative and anti-inflammatory properties. Thus, krill powder has a lot of potential in improving lipid and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The included studies were published between 2009 and 2018. Two were conducted in Japan [ 26 , 27 ], and the rest were conducted in Iran [ 28 ], Finland [ 29 ], Korea [ 30 ], Australia [ 31 ], and Canada [ 32 ]. The included studies comprised 17 treatment arms with a total of 321 participants (185 participants in the AST arm and 136 participants in the control arm).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies were published between 2009 and 2018. Two were conducted in Japan [ 26 , 27 ], and the rest were conducted in Iran [ 28 ], Finland [ 29 ], Korea [ 30 ], Australia [ 31 ], and Canada [ 32 ]. The included studies comprised 17 treatment arms with a total of 321 participants (185 participants in the AST arm and 136 participants in the control arm).…”
Section: Resultsmentioning
confidence: 99%
“…The sample sizes varied from 27 [ 30 ] to 63 [ 32 ]. The daily dosage of AST varied from 0.16 [ 29 ] to 20 mg [ 30 ]. Two studies reported outcomes in terms of different dosages of AST [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that its main components EPA and DHA play key roles in metabolic regulation [25]. In addition, KO also contains a dose of astaxanthin, which is believed to be responsible for the anti-inflammatory, antioxidant, analgesic, and lipid-lowering properties in vivo [26,27]. It has been found that KO improves intestinal flora structure and metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on krill protein for human consumption are very limited [30] and the AA profile after the ingestion of krill protein compared to other protein sources has not been studied previously in a human trial. The study revealed that all of the three protein sources significantly increased the total postprandial AA serum concentration at all timepoints between 20-120 min compared to CON.…”
Section: Discussionmentioning
confidence: 99%